2018
DOI: 10.3389/fped.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Administration in Juvenile Monkeys: Implications for Pharmacotherapy in Children

Abstract: Fluoxetine therapy has been approved for children with major depressive disorder and obsessive compulsive disorder for over 14 years and has expanded to other childhood behavior disorders. As use increases, more detail on fluoxetine effects during juvenile brain development can help maintain safe and effective use of this therapy. Here, a narrative review is provided of previously published findings from a large nonhuman primate project. Fluoxetine was administered to juvenile male rhesus monkeys for an extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Interaction between fluoxetine treatment and MAOA genotype has been shown not only for circulating metabolite levels in juvenile macaques, but for behavioral responses, as well [26,35]. In line with this observation, compared to the average, the 106 treatmentassociated lipids showed an increased number of treatment-by-genotype interactions identified using ANOVA (enrichment p < 10 −7 , Figure 3A; Table S6).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Interaction between fluoxetine treatment and MAOA genotype has been shown not only for circulating metabolite levels in juvenile macaques, but for behavioral responses, as well [26,35]. In line with this observation, compared to the average, the 106 treatmentassociated lipids showed an increased number of treatment-by-genotype interactions identified using ANOVA (enrichment p < 10 −7 , Figure 3A; Table S6).…”
Section: Resultssupporting
confidence: 70%
“…Additionally, in a previous study we detected a reduction of AA in the blood plasma of fluoxetine-treated macaques [26], further supporting the hypothesis that fluoxetine can introduce organism-wide fatty acid metabolism alterations. While we cannot make conclusions about causality, our previous studies including the same macaque individuals [24,29,35] demonstrated that these fluoxetine-related metabolic alterations were accompanied by behavioral alterations as well.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This dosage has been shown to reduce anxiety-related symptoms such as self-injuries and stereotypic behaviors in monkeys [37,38]. Drug concentrations and metabolic profiles are reported to be consistent with those seen in humans [42]. Fluoxetine administration was initiated after completion of experimental sessions defined as control days in which data was collected without any injection.…”
Section: Fluoxetine Administrationmentioning
confidence: 99%
“…Despite its significant pharmacological efficacy, there are no studies on the potential effects of fluoxetine on brain development in children. Notably, recent studies in nonhuman primates (NHPs) have documented persistent effects on sleep disturbance, sustained attention, and impulsivity after discontinuation of treatment ( Golub et al, 2017 ; Golub & Hogrefe, 2016 ; Golub et al, 2016a ; Golub et al, 2018 ; He et al, 2014 ). Furthermore, alterations in serotonin receptor binding and lipidomics have been detected in the brain one year after treatment cessation ( Golub et al, 2019 ; Tkachev et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%